MENEGUHKAN INOVASI PENDIDIKAN DALAM DISKURSUS AL-QUR’AN: KEBERMANFAATANNYA DI SEKOLAH-MADRASAH DI INDONESIA - Mohammad Jailani (Sekolah Tinggi Agama Islam Sadra, 2023)
In the era of modernization and in the current era of globalization, there are many demands and responsibilities for teachers, lecturers, professors, and Islamic educational institutions and Islamic research to innovate. Especially the policy makers the Ministry of Education and Culture and the Ministry of Religion, are required to innovate. In this millennial era, it is necessary to understand the Qur'an as a reference and Islamic literature as an innovation for the benefit of the ummah in all aspects. The method used in this research is qualitative research through literature study and analytical approach. The researcher captures all the literature stored in books on innovation from the Al-Qur'an perspective, innovation from Islamic education perspectives, and journals that are relevant to this paper. The researchers took research samples at schools and Madrasas in Yogyakarta, namely SMK Muhammadiyah 3 Yogyakarta and MA MBS Pleret Yogyakarta with the method of observation and interviews objectively and validation. Data analysis was carried out by content analysis referring to Miles and Huberman's theory. The results of this study found that based on the results of the formal and material object literature, changes in human life cannot be separated from innovation. Innovation is inseparable from something new, creative and adaptive to the times. Educational innovation is an attempt to make changes in order to obtain better results in education. Educational innovation is able to solve various challenges of the times and make education go hand in hand with other aspects of life. Whereas based on the field that innovations in the Qur'an are taught directly in class, if students are given Al-Qur'an material in an innovative way, good teaching, offers interesting discussions, especially the methods used by teachers for the majority of students at the school-madrasah level. underwent significant changes.